Smart solar power inverter: Solar power systems, inverters, photovoltaic, Internet of things (IoT). - Nair, Sheeja; Khunt, Muskaan Fatema; Jain, Janvhi (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The growth of the solar market over the past few years has been remarkable, with the increase in total number of installations of photovoltaic plants worldwide. The impact of this ever growing clean and efficient renewable energy generation makes it imperative that the grid infrastructure become more resilient and smart to produce uninterrupted flow of electricity. The research paper focuses on two main aspects viz. generation of electricity through solar energy and secondly connecting wireless communications to monitor the solar power inverter. The solar based inverter circuit along with Internet of Things (IoT) interfaced level indicator circuit. To indicate the amount of charge left and time consumption depending upon different load usage IoT devices are used to monitor.